Between orality and literacy : communication and adaptation in antiquity - Scodel, Ruth, 1952-; International Conference on Orality and Literacy in the Ancient World 2012 : Ann Arbor, Michigan) (Leiden : Brill, 2014)
The essays in Between Orality and Literacy address how oral and literature practices intersect. Their topics range from Homer and Hesiod to the New Testament and Gaius'Institutes, from epic poetry and drama to vase painting, historiography, mythography, and the philosophical letter.
Obsahuje bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: orální komunikace -- starověké Řecko; orální komunikace -- starověký Řím; písemná komunikace -- starověké Řecko; písemná komunikace -- starověký Řím; lidová slovesnost -- starověké Řecko; lidová slovesnost -- starověký Řím; textová transmise -- starověké Řecko; textová transmise -- starověký Řím; oral communication -- ancient Greece; oral communication -- ancient Rome; written communication -- ancient Greece; written communication -- ancient Rome; folk literature -- ancient Greece; folk literature -- ancient Rome; text transmission -- ancient Greece; text transmission -- ancient Rome; sborníky konferencí; e-knihy online; proceedings of conferences; e-books online